2022
DOI: 10.1186/s13063-022-06067-5
|View full text |Cite
|
Sign up to set email alerts
|

Animated, video entertainment-education to improve vaccine confidence globally during the COVID-19 pandemic: an online randomized controlled experiment with 24,000 participants

Abstract: Background Science-driven storytelling and entertainment-education (E-E) media demonstrate potential for promoting improved attitudes and behavioral intent towards health-related practices. Months after the outbreak of coronavirus disease 2019 (COVID-19), emerging research highlights the essential role of interventions to improve public confidence in the COVID-19 vaccine. To improve vaccine confidence, we designed three short, animated videos employing three research-informed pedagogical strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…This finding contrasts with the significantly higher grand mean hope score observed across a similar number of adult participants (N = 12,000) in China, who were involved in the parallel sister trial. 20 The mean hope score in this parallel study population fell within the medium hope score range. (F. Yu, personal communication, December 2021).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This finding contrasts with the significantly higher grand mean hope score observed across a similar number of adult participants (N = 12,000) in China, who were involved in the parallel sister trial. 20 The mean hope score in this parallel study population fell within the medium hope score range. (F. Yu, personal communication, December 2021).…”
Section: Discussionmentioning
confidence: 71%
“…Our survey was nested within a randomized controlled trial, described elsewhere. 20 The trial aimed to explore the effect of vaccine promotion media on vaccine hesitancy.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown high potential of entertainment-focused educational media as a powerful tool for promoting healthy behaviors ( 41 43 ). However, only a few studies have explored the potential of SAS videos in tackling vaccine hesitancy ( 44 , 45 ). In a systematic review, Shen and Han ( 46 ) concluded that techniques for measuring the impact of entertainment-focused instructional media are lacking, and they advocated conducting controlled studies to determine what features may result in desirable effects.…”
Section: Discussionmentioning
confidence: 99%
“…We define the difference between the SAS intervention videos and the control as the total effect, the difference between the SAS intervention videos and the APC video as the content effect, and the difference between the APC video and the control as the attention effect. There have been several entertainment-education studies that have employed an experimental approach to assess the effect of an intervention video in this way ( 47 51 ), but only few on COVID-19 ( 44 , 45 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the humorous message shown to participants in this study performed poorly, humor is increasingly used to reach social media audiences otherwise disengaged from a public health topic and promote widespread sharing [66][67][68]. Friendly, self-deprecating humor as seen in popular voice assistant bots may be a better choice for one-to-one anonymous conversations with a chatbot than meme-style humor [69].…”
Section: Principal Findingsmentioning
confidence: 99%